Blast responses of carbon-fiber reinforced polymer tubular columns filled with seawater sea-sand concrete. (15th December 2021) - Sun, Dawei; Xu, Ying; Wang, Peng; Zhou, Jiannan; Jin, Fengnian; Li, Hongying; Fan, Hualin
Highlights: CFFT columns were designed for protective structures. The quasi-static and dynamics mechanical performances of CFFT columns were investigated. The damage of exploded columns was evaluated. CFRP tube significantly improves the axial compression ability of the SSC. The blast resistance of the CFFT columns is significantly improved. Abstract: Concrete-filled fiber-reinforced polymer tubular (CFFT) columns are advanced structures in civil engineering due to their advantages of high strength, good corrosion resistance, and strong stability. In this study, four groups of columns were designed, with three groups of CFFT columns cast with carbon-fiber reinforced polymer (CFRP) tube and seawater sea-sand concrete (SSC) reinforced with glass fiber reinforced plastic (GFRP) bars and one group of reference SSC columns. Quasi-static compression and field explosion experiments were conducted to investigate their quasi-static and dynamics mechanical performances. The damage of exploded columns was evaluated by direct radiography (DR) inspection and residual bearing capacity testing. The quasi-static compression capacity of the CFFT column is about twice of the summation of the load bearings of the CFRP tube and the SSC column with the help of the constraint effect of the CFRP tube. An improved model was proposed to predict the compression capacity of the CFFT column considering the strength of the CFRP tube. The CFRP tube attenuates the spalling failure of SSC columns and transfers the damage to concrete tensile crack and CFRP damage. The innovative CFFT column filled with GFRP bars reinforced SSC exhibits immense potential in marine protective structures.